Product Development for Competitive Advantage of Micro, Small, and Medium Enterprises of Ikat Woven Fabric in Kediri - Rita Ambarwati; Andre Saputro; Aditya Galih Fathurochman; As'ad Rizal (Binus Business Review, 2019)
The research aimed to provide the solutions for the method of selecting product development strategies based on competitive advantage criteria including Quality, Cost, Delivery, Service, and Morale (QCDSM). The research was done in Micro, Small, and Medium Enterprises (MSMEs) of Ikat woven fabric in which the collecting data used questionnaires for the customers. The questionnaire was regarding the criteria for competitive advantage for MSMEs of Ikat woven fabric in Kediri. The analysis methods applied Importance-Performance Analysis (IPA) and Quality Function Deployment (QFD) based on the criteria of competitive advantage. The results show that the MSMEs of Ikat woven fabric should replace plastic materials into recyclable materials, ensure that raw materials do not contain dangerous and poisonous materials, choose coloring materials that do not contain dangerous and poisonous materials, choose the third parties to deliver products, weigh dye materials according to their composition and measurement, and utilize domestic raw materials.